1988
DOI: 10.3133/pp1484
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy of the Tertiary sediments in a 945-foot-deep corehole near Mays Landing in the southeastern New Jersey coastal plain

Abstract: The section from the early Eocene (Zone NP 12) through the early Oligocene (Zone NP 21) is nearly complete at this locality; in fact, it is one of the most complete sections through this part of the geologic column found anywhere to date in the U.S. Atlantic Coastal Plain. The presence of upper Eocene and lower Oligoeene sediments in the New Jersey Coastal Plain was heretofore unknown. Thus, informal names are:used for some units. All the Paleogene formations recovered in the core were deposited in a shelf env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 9 publications
(16 reference statements)
2
52
0
Order By: Relevance
“…These are quartz-quartzite-chert fluvial gravels and quartz-feldspar-chert sands that overlie the Cohansey Formation, a marginal-marine quartz sand of late middle Miocene age. The age of the Cohansey is based on pollen (Owens et al 1988) and on a Sr stable isotope age of 12 Myr for the youngest beds of the underlying Kirkwood Formation (Sugarman et al 1993). The Beacon Hill and Bridgeton are preserved in erosional remnants of broad fluvial plains, less than 12 m thick, capping the highest elevations in the Coastal Plain.…”
Section: Hudson Drainage In the Late Miocenementioning
confidence: 99%
“…These are quartz-quartzite-chert fluvial gravels and quartz-feldspar-chert sands that overlie the Cohansey Formation, a marginal-marine quartz sand of late middle Miocene age. The age of the Cohansey is based on pollen (Owens et al 1988) and on a Sr stable isotope age of 12 Myr for the youngest beds of the underlying Kirkwood Formation (Sugarman et al 1993). The Beacon Hill and Bridgeton are preserved in erosional remnants of broad fluvial plains, less than 12 m thick, capping the highest elevations in the Coastal Plain.…”
Section: Hudson Drainage In the Late Miocenementioning
confidence: 99%
“…Drilling on the continental slope (Leg 150) has proven to be very successful in this regard; quite surprisingly, onshore drilling (Leg 150X) in extreme updip settings has been remarkably successful as well owing to technological advances in dating (e.g., Sr-isotopic stratigraphy). In addition to recovering and dating Oligocene and younger sequences, onshore drilling at the ACGS#4 [Owens et al, 1988] (Figure 1), Island Beach, Atlantic City, and Cape May boreholes [Miller et al, , 1996a, recovered an excellent record of Eocene sequences. This older interval is particularly critical for evaluating mechanisms of eustatic change and the validity of sequence stratigraphy for global correlation.…”
Section: ]mentioning
confidence: 99%
“…The New Jersey margin (coastal plain, continental shelf, and continental slope; see Figure 1) is a classic passive continental margin that formed following Late Triassic-Early Jurassic rifting [Grow and Sheridan, 1988]. Postrift tectonics have been dominated by simple thermal subsidence and sediment loading (both Airy and flexural isostasy [Watts and Steckler, 1979;Reynolds et al, 1991] Previous onshore studies have been hampered by insufficient material for study: outcrops are deeply weathered, and virtually all previous rotary wells and boreholes were discontinuously sampled (the ACGS#4 borehole is a notable exception [Owens et al, 1988]). Continuous coring at Island Beach, Atlantic City, and Cape May addressed this problem by providing 4175 feet (1273 m) of core that allows identification and dating of Cenozoic sequences [Miller et al, , 1996a.…”
Section: Marginmentioning
confidence: 99%
“…The Cohansey Formation is an unconfined sand-and-gravel aquifer with discontinuous interbedded clays (Owens et al, 1988). The Kirkwood Formation is a fine to medium sand (Owens et al, 1988). Rhodehamel (1973) reported that the hydraulic conductivity of the Kirkwood-Cohansey aquifer system ranges from 90 to 250 ft/d, and values for specific locations were obtained from published regional groundwater flow models and the transmissivity ranges from 4000 to 8300 ft 2 /d.…”
Section: Introductionmentioning
confidence: 98%
“…Most of the PNR is underlain by the Kirkwood-Cohansey aquifer system, which underlies 3000 square miles of the New Jersey Coastal Plain (Watt, 2000). The Cohansey Formation is an unconfined sand-and-gravel aquifer with discontinuous interbedded clays (Owens et al, 1988). The Kirkwood Formation is a fine to medium sand (Owens et al, 1988).…”
Section: Introductionmentioning
confidence: 99%